Innovative thiosemicarbazones that induce multi-modal mechanisms to down-regulate estrogen-, progesterone-, androgen- and prolactin-receptors in breast cancer - Faten Shehadeh-Tout; Heloisa H. Milioli; Suraya Roslan; Patric J. Jansson; Mahendiran Dharmasivam; Dinny Graham; Robin Anderson; Tharushi Wijesinghe; Mahan Gholam Azad; Des R. Richardson; Zaklina Kovacevic (Pharmacological Research, 2023)
The estrogen receptor-α (ER-α) is a key driver of breast cancer (BC) and the ER-antagonist, tamoxifen, is a central pillar of BC treatment. However, cross-talk between ER-α, other hormone and growth factor receptors enables development of de novo resistance to tamoxifen. Herein, we mechanistically dissect the activity of a new class of anti-cancer agents that inhibit multiple growth factor receptors and down-stream signaling for the treatment of ER-positive BC. Using RNA sequencing and comprehensive protein expression analysis, we examined the activity of di-2-pyridylketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT) and di-2-pyridylketone-4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC), on the expression and activation of hormone and growth factor receptors, co-factors, and key resistance pathways in ER-α-positive BC. DpC differentially regulated 106 estrogen-response genes, and this was linked to decreased mRNA levels of 4 central hormone receptors involved in BC pathogenesis, namely ER, progesterone receptor (PR), androgen receptor (AR), and prolactin receptor (PRL-R). Mechanistic investigation demonstrated that due to DpC and Dp44mT binding metal ions, these agents caused a pronounced decrease in ER-α, AR, PR, and PRL-R protein expression. DpC and Dp44mT also inhibited activation and down-stream signaling of the epidermal growth factor (EGF) family receptors, and expression of co-factors that promote ER-α transcriptional activity, including SRC3, NF-κB p65, and SP1. In vivo, DpC was highly tolerable and effectively inhibited ER-α-positive BC growth. Through bespoke, non-hormonal, multi-modal mechanisms, Dp44mT and DpC decrease the expression of PR, AR, PRL-R, and tyrosine kinases that act with ER-α to promote BC, constituting an innovative therapeutic approach.